MANUFACTURING OF A VISCOMETER FOR MONITORING OIL CONTENT IN POLLUTED WATER - Souza, Roberto José Monteiro de; König, Annemarie (HOLOS, 2013)
Petroleum activities have been frequently associated to environmental damage due to occurrence of oil spill in worldwide sea waters. In addition to this problem it must be considered that many non-petrol companies process oil derivatives and discharge their rejection in rivers, accidentally or purposely. The monitoring of water contamination is usually carried out by government agencies, as well as by private committees. Therefore, population rarely becomes totally aware of the facts concerning oil contamination in rivers and seas, unless these committees and agencies publish accurate data about it. Social participation is an important demand as to promoting politically correct environmental management, however it is necessary to provide instrumental support to achieve this aim. In this work it is proposed a “do it yourself” viscometer designed to estimate oil rate in bodies of water contaminated by ship spill or industry discharge. The instrument includes, among other components: one electric drill, one DC – 6 volt motor and one multimeter. Results show their reliability on the basis that the instrument allows a procedure which is capable of measuring viscosity in immiscible solutions unlike conventional viscometers. The viscometer is suggested as a tool for Rapid Assessment Program, which can meet social technology availability in order to cover qualitative and quantitative parameters.